Navigating the Pedagogical Landscape: An In-Depth Review of the Educational Atmosphere in College Settings - Bhoi, Chandrasekhar (PT. Riset Press International, 2024)
This comprehensive review paper delves into the multifaceted dimensions of the educational atmosphere in college environments. Drawing on a wide range of scholarly perspectives, we explore the various factors that contribute to shaping the learning environment within higher education institutions. From pedagogical approaches to institutional policies, campus culture, and student experiences, this paper aims to provide a holistic understanding of the complex dynamics that define the educational atmosphere in colleges. By synthesizing current research findings, identifying key trends, and highlighting challenges and opportunities, our review seeks to inform educators, administrators, and policymakers in fostering a positive and enriching learning environment for students in higher education.